DC electric field effects on the electron dynamics in double rectangular quantum dots - Ramirez,H. Y. (2006)
The effect of a dc electric field on the temporal evolution of an electron in a double rectangular quantum dot is explored in this work. In the framework of the effective mass approximation, first-order scattering rates for interaction between confined electron-''free'' electron and electron-longitudinal acoustic phonon at room temperature are calculated in the high tunneling regime, and used to evaluate the dynamics of the population and coherence in the first three confined levels under a short ac electric field pulse. Small values of these rates dependent upon the bias field make feasible the emission of coherent radiation at terahertz range.